Attitude, behaviour and choice: the role of psychosocial drivers in water demand management in Singapore. Issue 1 (2nd January 2020) - Koh, Y.T. Rachel
ABSTRACT: The integration of environmental psychology into the broader domain of water demand research is a growing aspect of water policy. This article contends that effective water demand management policies can only be developed through an identification of the key psychosocial drivers of water use and conservation. By situating goal-framing theory in the context of residential water consumption in Singapore, the article analyzes the determinants of water conservation behaviour. Appealing for a shift away from policies designed to gratify people's hedonic and gain goals, it asserts that greater priority should be placed on strengthening people's normative goals towards water conservation.